2018
DOI: 10.1177/0890117118787078
|View full text |Cite
|
Sign up to set email alerts
|

Few European Adults are Living a Healthy Lifestyle

Abstract: Few European adults were practicing 5 healthy behaviors. This should be a message for governments and be considered in the establishment of preventive public policies in the areas of health and health education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…In addition, an unhealthy lifestyle with a lower number of healthy behavior factors has been linked to a higher risk of developing type 2 diabetes and cardiovascular diseases and to premature death [1517]. Another recent study based on the European Social Survey 2014 observed that only 5.8% of adults in Europe were adhering to five healthy behaviors with strong differences between the 20 countries under study [18]. Hungary with 1.3% and the Czech Republic with 1.9% were the countries with the lowest prevalence of five healthy behaviors and the United Kingdom with 8.6% and Finland with 9.2% were those with the highest prevalence [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an unhealthy lifestyle with a lower number of healthy behavior factors has been linked to a higher risk of developing type 2 diabetes and cardiovascular diseases and to premature death [1517]. Another recent study based on the European Social Survey 2014 observed that only 5.8% of adults in Europe were adhering to five healthy behaviors with strong differences between the 20 countries under study [18]. Hungary with 1.3% and the Czech Republic with 1.9% were the countries with the lowest prevalence of five healthy behaviors and the United Kingdom with 8.6% and Finland with 9.2% were those with the highest prevalence [18].…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study based on the European Social Survey 2014 observed that only 5.8% of adults in Europe were adhering to five healthy behaviors with strong differences between the 20 countries under study [18]. Hungary with 1.3% and the Czech Republic with 1.9% were the countries with the lowest prevalence of five healthy behaviors and the United Kingdom with 8.6% and Finland with 9.2% were those with the highest prevalence [18]. In Germany in 2009–10, 7.1% of women and 3.2% of men were adhering to five healthy behaviors and 29.1% of women and 17.8% of men showed at least four out of five healthy behaviors [19].…”
Section: Introductionmentioning
confidence: 99%
“…In 20 European countries, the most commonly reported healthy lifestyle factors were moderate alcohol intake (89.1%), sleep quality (83.1%), and non-smoking habits (75.7%). Adequate FV intake was reported by 21.0% of adults 7 . In 52 low and middle-income countries (2002)(2003), 78.0% of subjects had an insufficient FV intake 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the observance of 5 healthy lifestyle factors by adults (FV intake, physical activity, healthy BMI, nonsmoking habits, and moderate alcohol intake) has fallen from 15% to 8%, according to the National Health and Nutrition Examination Survey results from 1988-1994 and 2001-2006 6 . In 20 European countries, only 5.8% of adults report adherence to 5 healthy lifestyle factors (FV intake, physical activity, non-smoking habits, moderate alcohol intake, and good sleep quality) 7 . In Brazil, the 2013 National Health Survey has shown that 37.3% of the Brazilian population eat 5 or more FV servings a day, 22.5% practice leisure time physical activity, 14.5% currently smoke, and 13.7% report alcohol abuse 8 .…”
Section: Introductionmentioning
confidence: 99%
“…To become long-term, motivated, and healthy plant-based dieters, individuals need to change their lifestyle behaviors. A healthy and active lifestyle is associated with health and quality of life [ 28 ], while an unhealthy lifestyle, which also includes an unhealthy diet, is recognized as a major risk factor for the development of various chronic diseases and premature mortality [ 29 31 ]. Physical activity (PA) [ 32 ], sleep hygiene [ 33 ], and stress status [ 34 ] are well-established modifiers that play key roles in health and disease prevention.…”
Section: Introductionmentioning
confidence: 99%